Etika v sodobni britanski dramatiki - Troha, Gašper (Primerjalna književnost, 2017)
In the 1990s, Great Britain has produced a new form of dramatic literature and theatre that was subsequently described and defined by Aleks Sierz as "in yer face" theatre. The main features of this writing are shock and presenting things like rape, slaughter, masturbation, drug abuse etc. on stage. These are used in order to stir viewer's emotions of fear and revolt. However, Sarah Kane, one of the most famous writers of the genre, said she was trying to search for the remnants of humanity in the modern world. The paper focuses on the question, how this ethical dimension is written in texts that show us the radical dystopia of our world. Firstly, it analyses Sarah Kane's Blasted, which was one of the most controversial dramatic texts of the 1990s. Later on it looks into the further development of the British drama by taking into consideration In the Republic of Happiness (2012) by Martin Crimp, which also deals with a possibility of ethics in the present. Through the analysis and comparison of both texts it shows how ethics is inscribed in modern British drama and comes to a conclusion that ethics is possible in modern literature.
Keywords: Kane, Sarah, 1971-1999; literature and ethics; Crimp, Martin, 1956-; English drama; "in yer face" theatre; literatura in etika; angleška dramatika; gledališče "u fris"